PENGGUNAAN METODE KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR - Sejati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low mathematics learning outcomes of fifth-grade students at SDN 021 Tanjung Palas. The low learning outcomes were caused by several factors, including: (a) students’ difficulties in understanding abstract geometric elements and their properties, and (b) less engaging instructional methods, as teaching was dominated by lectures, discussions, and assignments. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning method. This research was conducted as classroom action research and implemented in two cycles. The results of the study indicated an improvement in students’ learning outcomes. Based on the baseline data, only 16 students (44.4%) achieved mastery learning. This number increased to 25 students (69.4%) in the first cycle and further increased to 32 students (88.9%) in the second cycle. These findings demonstrate that the application of the STAD cooperative learning method can improve mathematics learning outcomes of fifth-grade students at SDN 021 Tanjung Palas.